Revision of failed humeral head resurfacing arthroplasty - Streubel, Philipp N. (Int J Shoulder Surg, 2016)
PURPOSE: The purpose of this study is to assess the outcomes of a consecutive series of patients who underwent revision surgery after humeral head resurfacing (HHR). Our joint registry was queried for all patients who underwent revision arthroplasty for failed HHR at our institution from 2005 to 2010. Eleven consecutive patients (average age 54 years; range 38-69 years) that underwent revision of 11 resurfacing arthroplasties were identified. The primary indication for resurfacing had been osteoarthritis in six, glenoid dysplasia in two, a chondral lesion in two, and postinstability arthropathy in one patient. The indication for revision was pain in 10 and infection in one patient. Seven patients had undergone an average of 1.9 surgeries prior to resurfacing (range 1-3). MATERIALS AND METHODS: All patients were revised to stemmed arthroplasties, including one hemiarthroplasty, two reverse, and eight anatomic total shoulder arthroplasties at a mean 33 months after primary resurfacing (range 10-131 months). A deltopectoral approach was used in seven patients; four patients required an anteromedial approach due to severe scarring. Subscapularis attenuation was found in four cases, two of which required reverse total shoulder arthroplasty. Bone grafting was required in one glenoid and three humeri. RESULTS: At a mean follow-up of 3.5 years (range 1.6-6.9 years), modified Neer score was rated as satisfactory in five patients and unsatisfactory in six. Abduction and external rotation improved from 73° to 88° (P = 0.32) and from 23° to 32° (P = 0.28) respectively. Reoperation was required in two patients, including one hematoma and one revision for instability. CONCLUSION: Outcomes of revision of HHR arthroplasty in this cohort did not improve upon those reported for revision of stemmed humeral implants. A comparative study would be required to allow for definitive conclusions to be made.